Epicardium-myocardium crosstalk orchestrates heart development - Nusrat, Anika; Wu, Mingfu (Frontiers in Cell and Developmental Biology, 2025)
The epicardium is critical in heart development, functioning as a paracrine signaling hub and a source of progenitor cells. Bidirectional communication between the epicardium and myocardium, mediated by tightly regulated signaling networks, is essential for proper cardiac morphogenesis. This review presents a comprehensive overview of epicardium-myocardium crosstalk across species, emphasizing how this crosstalk influences epicardial epithelial-to-mesenchymal transition (EMT), fate specification of epicardium-derived cells (EPDCs), myocardial proliferation and growth, and coronary vasculature development. We critically assess decades of research elucidating key pathways—retinoic acid, fibroblast growth factor (Fgf), insulin-like growth factor (Igf), platelet-derived growth factor (Pdgf), transforming growth factor-β (Tgfβ), various transcriptional and epigenetic regulators, as well as calcium signaling mediated epicardial function—that coordinate these developmental processes. Additionally, we include detailed tables summarizing key experimental models and mechanistic insights that have shaped the field. This integrative analysis advances our current understanding of epicardial-myocardial crosstalk and highlights unresolved questions to guide future investigations into cardiac development and disease.